The impossibility of social choice and the possibilities of individual values: political and philosophical liberalism reconsidered - Werner Güth; Hartmut Kliemt (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
Though the social choice of social institutions or social results is impossible there is, strictly speaking, no social choice individual evaluations of social institutions or results trivially are possible. Such individual evaluations can be deemed liberal either because they emphasize political institutions that embody liberal values (political liberalism) or because individuals make up their mind in a specifically liberal way of forming ethical judgment (philosophical liberalism). Seen in this light the Paradox of Liberalism is of theoretical or philosophical interest but not a practical problem of political (institutional) liberalism.
Keywords: B3; B52; D6; D7; D71; 330; Philosophical liberalism; political liberalism; public choice; social choice; Liberalismus; Public Choice; Soziale Werte; Spieltheorie; Theorie